The Structuring Role of Marine Life in Open Ocean Habitat: Importance to International Policy - O'Leary, Bethan C.; Roberts, Callum M. (Frontiers in Marine Science, 2017)
Areas beyond national jurisdiction (ABNJ) lie outside the 200 nautical mile limits of national sovereignty and cover 58% of the ocean surface. Global conservation agreements recognise biodiversity loss in ABNJ and aim to protect ≥10% of oceans in marine protected areas (MPAs) by 2020. However, no agreed mechanism to create MPAs in ABNJ currently exists, and existing management is widely regarded as inadequate to safeguard biodiversity. Negotiations are therefore underway for an ‘internationally legally binding instrument’ (ILBI) to the United Nations Convention on the Law of the Sea to enable biodiversity conservation beyond national jurisdiction. While this agreement will, hopefully, establish a mechanism to create MPAs in ABNJ, discussions to date highlight a further problem: namely, defining what to protect. We have a good framework for terrestrial and coastal habitats, however habitats in ABNJ, particularly the open ocean, are less understood and poorly defined. Often, predictable broad oceanographic features are used to define open ocean habitats. But what exactly, constitutes the habitat - the water, or the species that live there? Complicating matters, species in the open sea are often highly mobile. Here, we argue that mobile marine organisms provide the structure-forming biomass and constitute ‘habitat’ in the open ocean. For an ABNJ ILBI to offer effective protection to marine biodiversity it must consider habitats a function of their inhabitants and represent all marine life within its scope. Only by enabling strong protection for every element of biodiversity can we hope to be fully successful in conserving it.